2019
DOI: 10.3762/bjnano.10.223
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force acoustic microscopy reveals the influence of substrate stiffness and topography on cell behavior

et al.

Abstract: The stiffness and the topography of the substrate at the cell–substrate interface are two key properties influencing cell behavior. In this paper, atomic force acoustic microscopy (AFAM) is used to investigate the influence of substrate stiffness and substrate topography on the responses of L929 fibroblasts. This combined nondestructive technique is able to characterize materials at high lateral resolution. To produce substrates of tunable stiffness and topography, we imprint nanostripe patterns on undeveloped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On this topic, Mih et al revealed the insensitiveness of L929 cells to substrates with stiffnesses in the 0.1–100 kPa range [ 49 ], comparable to the one investigated in the present study. Moreover, even substrates with higher E ranges (i.e., in the order of MPa) have been reported not to influence the spreading and the shape of L929 cells seeded on them [ 50 ]. Since the present study was intended as a bench test for crosslinked MC substrates to evaluate their responsive behavior in the field of CSE, the obtained outcomes should not be considered unfavorable.…”
Section: Resultsmentioning
confidence: 99%
“…On this topic, Mih et al revealed the insensitiveness of L929 cells to substrates with stiffnesses in the 0.1–100 kPa range [ 49 ], comparable to the one investigated in the present study. Moreover, even substrates with higher E ranges (i.e., in the order of MPa) have been reported not to influence the spreading and the shape of L929 cells seeded on them [ 50 ]. Since the present study was intended as a bench test for crosslinked MC substrates to evaluate their responsive behavior in the field of CSE, the obtained outcomes should not be considered unfavorable.…”
Section: Resultsmentioning
confidence: 99%
“…The results 117 demonstrate the uniqueness of SNFUH to image the internal structures of cell and the fine structures along cell periphery, which is useful for understanding the life activities of single cells. There are now commercially available products for realising the simultaneous AFM and ultrasound imaging of specimens (http://www.afm.cn), which have been utilised to the studies of single cells 123,124 . Nevertheless, it should be noted that so far SNFUH works well for simple biological systems such as RBCs (Figure 4B) which do not have organelles and specimens which have regular multilayer structures (Figure 4A).…”
Section: Combining Afm With Ultrasoundmentioning
confidence: 99%
“…7 In addition to physical signals, substrate elasticity and topography are two of the most critical physical cues in regulating cell functions and tissue regeneration. 8 The elasticity of biomaterials is a crucial factor in constructing the microenvironment during tissue regeneration. 9 Previous studies have shown that cell behavior is regulated by matrix elasticity, which plays an important role in mechanical transduction.…”
Section: Introductionmentioning
confidence: 99%